Konsep Tajalli ‘Abd al-Lāh Ibn ‘Abd al-Qahhār al-Bantanī dan Posisinya dalam Diskursus Wujūdiyyah di Nusantara - Ade Fakih Kurniawan (Universitas Islam Negeri Mataram, 2013)
This article aims to examine the wujūdiyyah teaching of ‘Abd al-Lāh bin ‘Abd al-Qahhār al-Bantanī in his Mashāhid al-Nāsik fī Maqāmāt al-Sālik. Although he was a great ulama in the period of Sultan Abū al-Naṣr ‘Ārif Shifā’ Zayn al-‘Āshiqīn—the ruler of Banten Sultanate in the eighteenth century—his name was rarely mentioned in the history of Banten. The Sultan asked him to write a book on wujūdiyyah that especially deals with tajalliyāt. The polemics over wujūdiyyah in Banten is different from those of Aceh. In Banten, there is no information whether the Sultan banned or considered the adherents of wujūdiyyah teaching as infidel (unbeliever). Regarding tajalliyāt, al-Bantani explains it in relation to the tajallī phases of God over the realm that he divides into four: ‘ālam ilāhī, ‘ālam jabarūt, ‘ālam malakūt and ‘ālam nāsūt. His concept about these worlds is different from al-Burhanpurī’s Martabat Tujuh and from those of Hamzah Fanṣūrī, al-Jīlī as well as Ibn ‘Arabī.",